Nitrous oxide emissions from cassava fields amended with organic and inorganic fertilizers. (19th January 2021) - Chirinda, Ngonidzashe; Trujillo, Catalina; Loaiza, Sandra; Salazar, Sandra; Luna, Jorge; Tong Encinas, Liz Alexandra; Becerra López Lavalle, Luis Augusto; Tran, Thierry
Abstract: Cassava production requires nitrogen (N) inputs to drive processes such as protein synthesis. Nevertheless, N not taken up by cassava roots is subjected to microbial transformation resulting in nitrous oxide (N2 O) production, a potent greenhouse gas. The temporal dynamics of soil N is partially influenced by the N source (i.e., organic or inorganic fertilizer) and the synchrony between N supply and demand. This study, which was conducted in Colombia on soils with high organic carbon and phosphorus contents, aimed at monitoring N2 O emissions from cassava plots fertilized with organic (49.8 kg N ha ‐1 year ‐1 ) or inorganic fertilizers (22.7 kg N ha ‐1 year ‐1 ). Although the organic fertilizer (vermicompost) contained more than double the amount of N, cumulative N2 O emissions from organic cassava production (1.28 kg N2 O‐N ha ‐1 ) were lower than those from inorganic fertilizer‐based cassava production (1.74 kg N2 O‐N ha ‐1 ) system. This finding indicates that, if crop yields can be maintained, there is potential to reduce cassava production's environmental impact through organic fertilization on highly fertile soils. However, a transition to organic fertilization depends on the availability of sufficient amounts of organic fertilizers at the farm level. The N2 O emissions in this study were higher than those predicted using the default IPCC emission factor, which confirmed the relevance of using country or regional specific emissions factors.